Sustainable Development of African Countries: Minding Public Life, Education, and Welfare - Danyang Li; Guosheng He; Hui Jin; Fu-Sheng Tsai; Fu-Sheng Tsai; Fu-Sheng Tsai; Fu-Sheng Tsai (Frontiers Media S.A., 2021)
Sustainable development (SD) has increasingly played a key background role in government policymaking across the world, especially for the least developed countries in Africa. Therefore, the purpose of our research is to study the SD of African countries in public life, education, and welfare, and then to help policy makers better monitor the status of sustainable development and formulate development policies in these aspects. We firstly propose a new method to assess the SD in public life, education, and welfare. Then we assess the SD status in 51 African countries as well as other countries in the world. After that, we also make a comparison between African countries and the countries in other continents.